The Strategy of Picornavirus Evading Host Antiviral Responses: Non-structural Proteins Suppress the Production of IFNs - Wang, Yining; Ma, Lina; Stipkovits, Laszlo; Szathmary, Susan; Li, Xuerui; Liu, Yongsheng (Frontiers in Microbiology, 2018)
Viral infections can trigger the innate immune system to produce interferons (IFNs), which play important roles in host antiviral responses. Co-evolution of viruses with their hosts has favored development of various strategies to evade the effects of IFNs, enabling viruses to survive inside host cells. One such strategy involves inhibition of IFN signaling pathways by nonstructural proteins. In this review, we provide a brief overview of host signaling pathways inducing IFN production and their suppression by picornavirus nonstructural proteins. Using this strategy, picornaviruses can evade the host immune response and replicate inside host cells.